Boat orientation & skill level in sculling boats - Loschner, C.; Galloway, M.; Smith, R. (coachesinfo.com, 2000)
The amount of yaw, pitch and roll induced in the boat by a sculler will affect the efficiency of boat propulsion. The purpose of this study was to analyse the movement of a rowing boat (Single Scull) in three dimensions and relate the results to the rowing style of the sculler. The study examines the relationship between the boat orientations and the seat and hand position. In rowing, the pitch of the boat is influenced by the movement of the seat and the rowers' body mass. The roll and yaw of the boat is dependent on the skill level of the athlete. All movement in any of these three directions will influence the boat velocity.